Asuhan Keperawatan pada Ny. S dengan Gangguan Sistem Pernapasan : Bronkopneumonia di Ruang Dahlia Rsud Dr. Soeselo Kabupaten Tegal - Septiana Nur Salsabila; Esti Nur Janah; Ahmad Zakiudin (Calory Journal Medical Laboratory Journal, 2024)
Bronchopneumonia is an inflammation of the lung parenchyma that extends to the bronchioles, which can be understood as inflammation of the lung tissue with direct spread through the respiratory tract to the bronchi (Hapsari et al., 2022). The purpose of this writing is to understand the nursing care process for Mrs. S with respiratory system disorders: bronchopneumonia in Dahlia Ward, RSUD dr. Soeselo Tegal Regency. This writing method uses a descriptive approach with a nursing process approach. The results of the nursing care found that the patient had shortness of breath, productive cough, and ronchi sounds; the patient and family were unaware of the disease. The nursing diagnoses identified were ineffective airway clearance and knowledge deficit. Interventions were carried out based on SIKI (Indonesian Standard for Nursing Care) and implementation was based on the designed interventions. Evaluation of the two diagnoses revealed that one diagnosis, the knowledge deficit, was resolved, while the issue of ineffective airway clearance was partially resolved. The results of the nursing care were consistent with the theory. This writing is expected to improve skills in providing nursing care.